2003
DOI: 10.1142/s0218127403006601
|View full text |Cite
|
Sign up to set email alerts
|

Parameter-Induced Stochastic Resonance and Baseband Binary Pam Signals Transmission Over an Awgn Channel

Abstract: From the point of information theory, the baseband binary pulse amplitude modulated (PAM) signals transmission, via tuning the nonlinear receiver's parameters, is studied over an additive white Gaussian noise (AWGN) channel. It is demonstrated that the channel capacity of baseband binary communication systems, for a given signal added noise, can be maximized by optimal designed receivers. This new form of stochastic resonance (SR) is referred to as parameter-induced stochastic resonance (PSR) in a broad sense.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 34 publications
0
61
0
1
Order By: Relevance
“…Researchers [77]- [79] have found noise benefits in DCT-domain watermark decoding based on parameter-induced stochastic resonance [80]. Their approaches differed from ours in two main ways.…”
Section: Watermark Embeddingmentioning
confidence: 85%
“…Researchers [77]- [79] have found noise benefits in DCT-domain watermark decoding based on parameter-induced stochastic resonance [80]. Their approaches differed from ours in two main ways.…”
Section: Watermark Embeddingmentioning
confidence: 85%
“…In the field of statistical signal processing, noise benefits are investigated in various studies such as [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. In [2], it is shown that the detection probability of the optimal detector for a described network with nonlinear elements driven by a weak sinusoidal signal in white Gaussian noise is non-monotonic with respect to the noise power and fixed false alarm probability; hence, detection probability enhancements can be achieved via increasing the noise level in certain scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…One approach for realizing noise benefits is to tune the parameters of a nonlinear system, as employed, e.g., in [8][9][10][11][12]. An alternative approach is the injection of a random process independent of both the meaningful information signal (transmitted or hidden signal) and the background noise (undesired signal).…”
Section: Introductionmentioning
confidence: 99%
“…Hence the BER is a percentage number. Some works, which tried to realize ASR by tuning system parameters to get the minimum BER, are known as parameter-induced ASR [15][16][17]. A Comparison between noise-induced ASR and parameter-induced ASR can be found in Ref.…”
Section: Introductionmentioning
confidence: 99%